2021
DOI: 10.18203/2349-2902.isj20210374
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of mammography and sonomammography and its correlation with histopathology in the detection of breast cancer

Abstract: Background: Mammography (MMG) plays a pivotal role in the early diagnosis of breast cancer (BC). However, it is sometimes difficult to use it to diagnose palpable breast lesions among young patients. Ultrasound can be used as an adjunct in differentiating cystic and solid masses. Studies evaluating the combination of MMG and sonomammography (SMG) as an adjunct to detect Breast cancer, are quite scarce in the literature. This study aimed to assess the accuracy of MMG and to comprehend the role of ultrasound as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
3
1
1
Order By: Relevance
“…There were 88 individuals with thick breasts in this research. This is consistent with Yamakanamardi and Hiremath (17) , who said that there were 90 patients in all of the instances. The patients were between the ages of 40 and 65.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…There were 88 individuals with thick breasts in this research. This is consistent with Yamakanamardi and Hiremath (17) , who said that there were 90 patients in all of the instances. The patients were between the ages of 40 and 65.…”
Section: Discussionsupporting
confidence: 91%
“…The patients were between the ages of 40 and 65. Between the ages of 40 and 50, where there were the most instances (85.3% of all cases), This is consistent with the research by Yamakanamardi and Hiremath (17) , which found that the majority of patients with malignant breast lesions were between the ages of 41 and 50.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sonomammography (diagnostic or targeted ultrasound) is a high-resolution ultrasound of the breast and it plays an important role in the evaluation of breast cancer [5]. It is effective in differentiating solid and fluid-containing masses.…”
Section: Introductionmentioning
confidence: 99%